92.7k views
2 votes
3x - 5x + 4 = 10

A. -7
B. 7
C. 3
D. -3

2 Answers

7 votes
Hey!


To solve this equation, we must first combine similar elements.

Original Equation :
3x - 5x + 4 = 10

New Equation {Changed by Combining Similar Elements} :
-2x + 4 = 10

Now that that's done, we'll move onto the second step. Which is to subtract 4 from both sides.

Old Equation :
-2x + 4 = 10

New Equation {Added Subtract Both Sides by 4} :
-2x + 4 - 4 = 10 - 4

Solution {New Equation Solved} :
-2x = 6

Now we divide both sides by two to get our final answer.

Old Equation :
-2x = 6

New Equation {Added Divided Both Sides by -2} :

(-2x)/(-2) =
(6)/(-2)

Solution {New Equation Solved} :
x = -3

So, now we know that in the equation 3x - 5x + 4 = 10, x = -3

Hope this helps!


- Lindsey Frazier ♥
User Grrrrrr
by
5.0k points
3 votes

3x-5x+4=10\\\\-2x+4=10\ \ \ |-4\\\\-2x=6\ \ \ |:(-2)\\\\x=-3
Answer: D. -3

User Adrian Nesta
by
5.0k points